ChemInform Abstract: Chemical Designs of Functional Photoactive Molecular Assemblies. Issue 31 (5th August 2014) - Yan, Qifan; Luo, Zhouyang; Cai, Kang; Ma, Yuguo; Zhao, Dahui
Abstract Review: 121 refs.